Disparities in surgical treatments for stress, urge and mixed urinary incontinence: Evidence from the 2019 National Ambulatory Surgery Sample (NASS) - Christabel Egemba; Edie Duncan; Katherine Amin; Alan Wein; Alberto J. Caban-Martinez; Raveen Syan (Continence)
Purpose:: Treatment of urinary incontinence (UI) is influenced by severity of symptoms and knowledge of available treatments. However, the relationship between race/ethnicity, socioeconomic status and receiving treatment is poorly understood. We aim to characterize differences in surgical management of urinary incontinence subtypes (Stress UI (SUI), overactive bladder (OAB), Mixed UI (MUI)) and identify predictors of receiving the indicated surgical treatment for each. Methods:: Using the 2019 National Ambulatory Surgery Sample (NASS) we used weighted data to identify 44,996 adult females with OAB, 87,737 with SUI, and 22,873 with MUI. Chi-square analysis was used to compare surgical treatments for each diagnosis, with significance assessed at <0.05. Multivariable logistic regression models estimated the associations between socioeconomic factors of receiving the indicated treatment for OAB, SUI, or MUI. Results:: Approximately 2.5% of the study population received surgical treatment for SUI, OAB or MUI. Sling was the most utilized surgical treatment for both SUI and MUI, at 75.2% and 60.8 % respectively. While SNS was the most utilized surgical treatment for OAB, 75% of OAB patients did not undergo surgical treatment. When considering age, insurance status, and income, Black women were significantly less likely to receive surgical treatment for MUI, OAB and SUI (0.69 [0.59, 0.80], 0.69[0.62, 0.76], 0.71 [0.65, 0.77]) respectively. Conclusion:: Among female patients with UI, certain factors predict whether a patient will receive surgical treatment, including race, insurance status, and income level. These findings could inform further research to examine the factors contributing to the disparities seen.